2017
DOI: 10.1002/2016jc012273
|View full text |Cite
|
Sign up to set email alerts
|

Combined observations of Arctic sea ice with near‐coincident colocated X‐band, C‐band, and L‐band SAR satellite remote sensing and helicopter‐borne measurements

Abstract: In this study, we compare colocated near‐coincident X‐, C‐, and L‐band fully polarimetry SAR satellite images with helicopter‐borne ice thickness measurements acquired during the Norwegian Young sea ICE 2015 (N‐ICE2015) expedition in the region of the Arctic Ocean north of Svalbard in April 2015. The air‐borne surveys provide near‐coincident snow plus ice thickness, surface roughness data, and photographs. This unique data set allows us to investigate how the different frequencies can complement one another fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 48 publications
2
50
0
1
Order By: Relevance
“…The N‐ICE2015 experiment also provided a valuable platform for validation of remote sensing products, from both satellite and airborne observations. Unique near‐coincident synthetic aperture radar (SAR) data at multiple frequencies and simultaneous ground truth could be gathered, that provided new insights into use of imagery for detection of open water and thin ice and for sea ice classification (Espeseth et al, ; Johansson et al, ; Ressel et al, ; Rösel et al, ).…”
Section: Overview Of Conditions During Experiments and Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N‐ICE2015 experiment also provided a valuable platform for validation of remote sensing products, from both satellite and airborne observations. Unique near‐coincident synthetic aperture radar (SAR) data at multiple frequencies and simultaneous ground truth could be gathered, that provided new insights into use of imagery for detection of open water and thin ice and for sea ice classification (Espeseth et al, ; Johansson et al, ; Ressel et al, ; Rösel et al, ).…”
Section: Overview Of Conditions During Experiments and Main Findingsmentioning
confidence: 99%
“…The N-ICE2015 experiment also provided a valuable platform for validation of remote sensing products, from both satellite and airborne observations. Unique near-coincident synthetic aperture radar (SAR) data at multiple frequencies and simultaneous ground truth could be gathered, that provided new insights into use of imagery for detection of open water and thin ice and for sea ice classification (Espeseth et al, 2016;Johansson et al, 2017Johansson et al, , 2018Ressel et al, 2016;R€ osel et al, 2017). King et al (2018) showed that radar reflections from both CryoSat-2 and an airborne radar instrument were closer to snow freeboard than ice freeboard, resulting in a systematic overestimation of sea-ice thickness in the N-ICE2015 region in spring 2015 by a factor of two in all operational CryoSat-2 products of date, despite of low temperatures (below 2158C).…”
Section: Sea Ice Remote Sensingmentioning
confidence: 99%
“…C-band SAR imagery has been widely used for sea ice extent and area classification as well as concentration estimation [13,14]. This is because C-band SAR frequency provides a good compromise Regional sea ice charts produced by Environment and Climate Change Canada at the CIS were acquired for this study from the CIS website (https://www.ec.gc.ca/glaces-ice/).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we want to explore sea ice classification on full-polarimetric data with secondary priority given to resolution, which naturally comes at the price of a smaller footprint. A list of the datatakes with the respective technical details can be found in [5,1] (and figures therein). We remark that each acquisition consists of two or three frames (frame corresponds to nominal acquisition length in azimuth direction).…”
Section: Datasetmentioning
confidence: 99%